Overview on Vocational Education and Skill Development: Exploring the concept and development of apprenticeships in vocational education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Apprenticeships are one of the most established, yet most famous types of training at the interface of work and learning and additionally the expression of education and the universe of work. In the principal section, we examine the attributes of various types of apprenticeships, for example, rationale, convention, work, learning and teaching. In the second section, we talk about various ideal models which regularly lead to misconceptions about the concept of apprenticeship (1) the private-training-showcase worldview, (2) the youngster worldview, (3) the propelled economy worldview and huge organization worldview, (4) the low-talented and industrial laborer worldview, (5) the specialized and men worldview, and (6) the discrimination worldview. In the third section we condense the outcomes in an Apprenticeship Maturity Model with six levels (1) informal apprenticeships, (2) semiformal apprenticeshipstime-served apprenticeships, (3) yield arranged apprenticeships, (4) input-situated apprenticeships, (5) process-arranged apprenticeships, and (6) aggregate apprenticeships. The proposed Apprenticeship Maturity Model follows an improvement rationale A problem emerges, is then tended to, and may be fathomed, and another problem emerges. This procedure prompts an improvement with various concepts of apprenticeship which can be portrayed regarding development levels.